1914
DOI: 10.1029/te019i004p00219
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of certain causes responsible for uncertainty in the measurement of atmospheric conductivity by the Gerdien conductivity apparatus

Abstract: One of the most convenient methods of measuring the atmospheric conductivity is that due to Gerdien. In this method a stream of air is drawn through the space between two concentric cylinders, the inner one of which is charged. By observing the fall of potential of the inner cylinder in a known time, it becomes possible to calculate the conductivity due to those ions which are of opposite sign to the charge on this cylinder. Since the theory of the instrument, as worked out by Gerdien, postulates certain condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1933
1933
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Correction to the ion density profiles. The computed value of ion density is dependent on the air flow rate through the condenser (G in equation 3 shown originally by Hewlitt [1914] that conductivity measurement by a Gerdien condenser is unaffected by the shape of the velocity profile across the condenser. However, it can be shown (see appendix) that if the profile alters from one point.…”
Section: And Investigationsmentioning
confidence: 99%
“…Correction to the ion density profiles. The computed value of ion density is dependent on the air flow rate through the condenser (G in equation 3 shown originally by Hewlitt [1914] that conductivity measurement by a Gerdien condenser is unaffected by the shape of the velocity profile across the condenser. However, it can be shown (see appendix) that if the profile alters from one point.…”
Section: And Investigationsmentioning
confidence: 99%
“…It is noted that some of the analysis presented is similar to that considered for conductivity measurements and early terrestrial charge density measurements; these earlier studies can be found in widely scattered publications [4,9,10,11,12]. Because of the current interest in monopolar charge density and net space charge density measurements near high voltage dc transmission lines, it is considered desirable to bring together in one short account information that can be used to help minimize errors during measurements of these quantities performed in the presence of relatively large dc electric fields.…”
Section: Introductionmentioning
confidence: 75%
“…Because of the electric field direction in the above example, the number of positive ions arriving at the cage is increased, However, as for ion counter measurements, theoretical arguments [4] supported by experimental results [6,9] indicate that the extra ions due to the electric field will not enter the interior of the Faraday cage provided that the electric field shielding is adequate.…”
mentioning
confidence: 96%